English Teachers Perception of Using Game-Based Learning (GBL) to Enhance Students’ Vocabulary - Purba, Febri A.; Katemba, Caroline V. (8ISC Proceedings: Arts and Education; 8ISC Proceedings: Arts and Education, 2022)
Game-based learning (GBL) is a tool used by academicians to teach learners about English for vocabulary. Vocabulary is crucial in learning the language; it is used to construct sentences, for communication, and especially improving the four skills (listening, speaking, reading, and writing). The lack of vocabulary is one of the aspects that make students lazy in learning the language. As we know, during this pandemic, there are so many educational technologies in the form of games used in teaching. Teachers use the game as a method to reduce students’ boredom while studying. This research aimed to find out teachers’ perceptions of using game-based learning in their classes. There were 40 high school teachers from Sumatra Island and Java Island who participated in this study. Questionnaires were distributed online using Google Forms. The finding of this research shows that the teachers’ perception of using game-based learning (GBL) is very good. They agree that using game-based learning not only enhances students’ vocabulary but also reduces students’ boredom in learning. Keywords : game-based learning, vocabulary, gamification